ANALISIS LINEAR RESPONSIBILITY PADA PENGELOLAAN WISATA HERITAGE STUDI LOKASI: KAWASAN HERITAGE KOTATUA JAKARTA - Annisa Magfirah Ramadhani; Dini Indriati (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2023)
Abstract: World heritage protection is an important component of basic government services. Heritage resources are valuable legacies from their predecessors which are in a state of vulnerability and cannot be renewed. When the government determines the ownership of cultural heritage resources, the government is also responsible and obligated in terms of protecting it from damage and keeping it sustainable. Another requirement is that this heritage also has public rights resources in it. For this reason, the government needs to make efforts to make managerial rules to ensure that inheritance is used rationally and fairly. The government also guarantees the protection of the same community rights to use it so that inheritance does not become a tool for profit for some people or groups. Kotatua Jakarta is a historical area that has been designated by the government as a historical tourism area. The Kotatua area of Jakarta is divided into three neighborhood groups. The environmental cluster whose position is most vital is this zone because in it there are historic buildings that are still preserved today. Management of cultural heritage areas is not easy, considering that the objects and buildings in them have high historical value. Crucial problems that occur in the area management process are not only physical in nature, but also managerial and administrative in nature. The physical problems that occur at the location are of course also directly related to the managerial system. The management of the Kotatua Jakarta cultural heritage area which is still lacking is exacerbated by non-physical problems in the area. This research has a definite goal, namely to formulate in detail the physical and non-physical problems as a first step, then analyze who the parties are involved in all management activities, compare them with the best practices that have been selected, so that the output obtained can be in the form of directions so that this does not happen. overlapping in the implementation of appropriate management and management systems for the Kotatua Jakarta area as a historical tourism area.Keyword: : Kotatua, regional management, linear responsibilityAbstrak: Perlindungan warisan dunia merupakan satu dari sekian komponen penting dari pelayanan dasar pemerintahan. Sumber daya yang berupa pusaka peninggalan adalah warisan berharga dari pendahulunya yang berada pada kerentanan dan kondisi tidak terbarukan. Ketika pemerintah menetapkan kepemilikan atas sumber daya pusaka maka pemerintah juga bertanggung jawab serta berkewajiban dalam hal perlindungan terhadap kerusakan dan menjaga agar berkelanjutan. Kondisi lainnya, warisan pusaka ini juga memiliki sumber daya hak publik di dalamnya. Untuk itu pemerintah perlu berupaya membuat aturan manajerial dalam memastikan warisan tersebut digunakan secara rasional dan adil. Pemerintah juga memastikan perlindungan hak masyarakat yang sama untuk memanfaatkannya agar warisan tidak menjadi alat penghasil keuntungan bagi sebagian orang atau kelompok. Kotatua Jakarta merupakan kawasan bersejarah yang telah ditetapkan oleh pemerintah sebagai kawasan wisata sejarah. Kawasan Kotatua jakarta terbagi menjadi tiga golongan lingkungan. Golongan lingkungan yang kedudukannya paling vital adalah zona ini karena berisi bangunan-bangunan sejarah yang kelestariannya masih dijaga sampai saat ini.Â Pengelolaan kawasan heritage bukanlah hal yang mudah, mengingat benda-benda serta bangunan-bangunan di dalamnya memiliki nilai historis yang tinggi. Masalah-masalah krusial yang terjadi pada proses pengelolaan kawasan tidak hanya pada fisiknya, tetapi juga pada manajerial dan administrasi pengelolaan. Masalah fisik yang terjadi pada lokasi tentu saja juga ikut berhubungan langsung dengan sistem manajerialnya. Pengelolaan kawasan heritage Kotatua Jakarta yang masih kurang ditambah oleh adanya permasalahan non fisik pada kawasan. Penelitian ini memiliki tujuan pasti yaitu merumuskan permasalahan detail secara fisik dan non fisik sebagai langkah awal, kemudian menganalisis siapa saja pihak-pihak yang terlibat dalam segala aktivitas pengelolaan, membandingkan dengan best practice yang telah dipilih, agar keluaran yang diperoleh dapat berupa arahan untuk menghindari terjadinya tumpang tindih dalam pelaksanaan pengelolaan serta sistem manajemen yang tepat untuk kawasan Kotatua Jakarta sebagai kawasan wisata sejarah.Kata Kunci: Kotatua, pengelolaan kawasan, linear responsibility